The essential Drucker : - Drucker, Peter F. (Collins Business Essentials, 2001)
Management as social function and liberal art. The dimensions of management. The purpose and objectives of a business. What the nonprofits are teaching business. Social impacts and social problems. Management's new paradigms. The information executives need today